The path to grammaticalization of the phrase "taking into account": the specifics of lexical and semantic compatibility - Dai, Xiahong (Филология: научные исследования, 2024)
As a result of the constant process of grammaticalization, a large number of words have appeared in the Russian language that perform the function of prepositions. Modern linguists are paying more and more attention to such service words. The object is the word "considering" (phrase "taking into account"), which performs a function similar to the function of a preposition. The subject of the study is the semantics and syntagmatic properties of this word form. The purpose of the study is to identify the syntagmatic specifics of the phrase "taking into account". The task is to establish thematic groups of vocabulary, which occupies the positions of the left and right components of the structure, which is built using the phrase "taking into account". The author examines in detail the specifics of the lexical and semantic compatibility of the phrase "taking into account" and its grammaticalization stage. The source of the material is the National Corpus of the Russian Language. The results obtained can be applied in lexicographic practice. The study uses a descriptive method and a method of contextual analysis. As a result of the analysis of the material, several lexico-semantic groups with the highest frequency of occurrence in the left and right components of the structure were identified. It has been established that the following lexical and semantic groups are the most frequent in the position of the right component: verbal nouns denoting human action and activity; nouns denoting parameters; nouns naming various kinds of qualitative characteristics; nouns naming phenomena from the sphere of "finance". In the position of the left component, verbs or verbal nouns with the meaning of creative activity are most frequent; vocabulary denoting a change in state or quantity; verbs and verbal nouns with the meaning of doing something. The interrelationships between lexical and semantic groups in the position of the left and right components are revealed. This allowed us to conclude about the limited compatibility of the phrase "taking into account", which indicates the initial stage of grammaticalization. The novelty of the research lies in the fact that the work presents for the first time the results of a study of the specifics of the syntagmatics of the word form "taking into account".